Self-regulating functions of L1 private speech during pre-university collaborative L2 reading / Farideh Yaghobian, Moses Samuel and Marzieh Mahmoudi - Yaghobian, Farideh; Samuel, Moses; Mahmoudi, Marzieh (Penerbit UiTM (UiTM Press), 2017)
This article reports on a study of how L1 was used by Persian speaking Pre-university learners of English in their private speech while interacting as they were engaged in L2 reading. The study was conducted in a real classroom setting in an Iranian school with the objective of better understand the mediating and regulatory role of L1 private speech in L2 reading. The analysis reveals that learners produced L1 private speech while interacting collaboratively with peers in social context. It presents evidence that L1 was utilized in learners’ self-talk as repetitions, affective utterances, pause fillers, self-directed questions and explanations, self-addressed negations, and self-addressed directives. This served learners cognitive and affective functions and assisted them to focus on the challenging part of the task and to maintain self-regulation. This study provided support for the theoretical orientation that views language not only as a means of communication but as a cognitive tool used to control one’s mental activity. It is hoped to contribute to the body of knowledge on SLA and sociocultural perspective of language learning by illustrating evidence for a shift from being othermediated or object mediated to guiding oneself and being self-mediated in the process of L2 classroom learning.